O poder político de José Américo de Almeida: a construção do americismo (1928-1935) - Silva, Bárbara Bezerra Siqueira (2015)
This dissertation aims to analyze the formation of the political power of José Américo de Almeida, known as americismo, in the period from 1928 to 1935. For a better understanding of this period discussed his ascension in the political scenario of Paraíba, still in the year 1928, at the invitation of the then President of Paraíba, João Pessoa. At that time we highlight their participation as Secretary of Public Security of the State, during the revolt of Princess, as well as its passage in the political command of Paraíba after João Pessoa and their participation and performance in the so-called "revolution of 1930”. In the case of americismo growth in Paraíba and the performance of José Américo de Almeida, the front of the provisional Government in the North/Northeast, seek support in the political history and the concept of political cultures. Other relevant period in the history of Almeida was the arrival at the Ministry of ways and public works in the interim Government of Getúlio Vargas highlighting its action in combating drought and the scourge in the region, in addition to the use of the Federal Inspectorate Works Against droughts for growth of this group and its name beyond the borders of the State. Also gave emphasis the political post in Paraíba rearticulations 30, seeking to understand what factors contributed to the expulsion of Almeida of politics in the year 1935 Paraíba. To carry out this research use the Union newspaper, the years from 1930 to 1934, research also in the collection of the foundation Casa de José Américo, where there is a rich iconographic material, as well as letters and telegrams received and dispatched.